2012
DOI: 10.1128/jvi.00309-12
|View full text |Cite
|
Sign up to set email alerts
|

The “Bridge” in the Epstein-Barr Virus Alkaline Exonuclease Protein BGLF5 Contributes to Shutoff Activity during Productive Infection

Abstract: Replication of the human herpesvirus Epstein-Barr virus drastically impairs cellular protein synthesis. This shutoff phenotype results from mRNA degradation upon expression of the early lytic-phase protein BGLF5. Interestingly, BGLF5 is the viral DNase, or alkaline exonuclease, homologues of which are present throughout the herpesvirus family. During productive infection, this DNase is essential for processing and packaging of the viral genome. In contrast to this widely conserved DNase activity, shutoff is on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 55 publications
4
36
0
Order By: Relevance
“…Separately, it was demonstrated that antibodies in sera of NPC patients could neutralise a viral alkaline exonuclease (DNAse) function which had diagnostic relevance, but only when using native DNAse enzyme prepared from P3HR1 cells (Cheng et al 1980;Stolzenberg et al 1996;Middeldorp and Ooka unpublished data). This proved to be due to small amino acid variations between type 1 (B95-8 prototype) and type 2 (AG786, P3HR1 prototype) EBV strains altering the antigenic structure of the EBV DNAse, but not its function (Liu et al 1998;Paramita et al 2007;Horst et al 2012). In 1983, Glaser et al, described first evidence that EA(R) was encoded by a distinct gene compared to EA(D), which subsequently is defined as the BHRF1 open reading frame, encoding the 17 KDa viral Bcl-2 homologue.…”
Section: The Ea Complexmentioning
confidence: 94%
“…Separately, it was demonstrated that antibodies in sera of NPC patients could neutralise a viral alkaline exonuclease (DNAse) function which had diagnostic relevance, but only when using native DNAse enzyme prepared from P3HR1 cells (Cheng et al 1980;Stolzenberg et al 1996;Middeldorp and Ooka unpublished data). This proved to be due to small amino acid variations between type 1 (B95-8 prototype) and type 2 (AG786, P3HR1 prototype) EBV strains altering the antigenic structure of the EBV DNAse, but not its function (Liu et al 1998;Paramita et al 2007;Horst et al 2012). In 1983, Glaser et al, described first evidence that EA(R) was encoded by a distinct gene compared to EA(D), which subsequently is defined as the BHRF1 open reading frame, encoding the 17 KDa viral Bcl-2 homologue.…”
Section: The Ea Complexmentioning
confidence: 94%
“…Both mutations abolish the ability of UL12 to complement the growth defect of a UL12-null mutant virus (29). Mutagenesis of EBV, HCMV, and KSHV UL12 orthologs has also demonstrated that residues analogous to UL12 G336, S338, and D340 are critical for nuclease activity (30,(32)(33)(34). We included three additional mutations that have also been shown to eliminate detectable nuclease activity in vitro and abolish complementing activity in vivo; ⌬N, L150K, and ⌬C (23).…”
Section: Resultsmentioning
confidence: 99%
“…This process, termed shutoff, is mediated by the EBV DNase (alkaline exonuclease) BGLF5, which is expressed with early kinetics during the productive phase of infection (Zuo et al 2008). BGLF5's additional RNase function utilizes the same catalytic site as its DNase activity, yet the substrate-binding site appears only partly shared by DNA and RNA substrates (Horst et al 2012). The promiscuous RNA degradation induced by EBV BGLF5 can affect immunologically relevant proteins, including TLR2 and TLR9 that are capable of sensing EBV infection (Gaudreault et al 2007;van Gent et al 2011van Gent et al , 2015.…”
Section: Reduction Of Toll-like Receptor Expressionmentioning
confidence: 99%